Synthesis and odour evaluation of allenic derivatives - Diaf, Ilhem; Joffrin, Amélie; Lemière, Gilles; Duñach, Elisabet (Flavour and fragrance journal, 2015)
A series of readily available allenic aldehydes and their alcohol, acetate and enol ether derivatives have been prepared and evaluated for their olfactory properties. The tested compounds revealed interesting fruity, floral and woody aspects as the main notes. Copyright © 2015 John Wiley & Sons, Ltd.